Dosimetric Verification of Computed Tomography (CT) Systems Using CTDI Phantom - Akter, Shirin; Khatun, Rajada; Kabir, S M Enamul; Monika, Ashrafun Nahar; Uddin, Md Fakhar; Rahman, Md Mahfuzur; Ahasan, Mohammad Monjur (Bangladesh Journal of Nuclear Medicine, 2024)
Background: Computed tomography (CT) is a medical imaging modality that contributes widely over the world for the diagnosis of disease and for treatment planning in the radiotherapy department. The purpose of the study is to measure the accuracy of dose of CT System for quality treatment. Materials and Methods: The study was executed in a 16 slice SOMATOM Emotion CT Scanner of Delta Hospital Ltd. with Tube voltage 130 KV and Tube current 25 mA using Computed Tomography Dose Index (CTDI) phantom (CIRS) of MPD, Atomic Energy Centre, Dhaka. IBA pencil ionization chamber was used to measure the dose at different positions inside the CTDI phantom and data were collected using IBA MagicMax Universal software. The CT radiation doses were estimated using formalisms in the AAPM Report 96 and 111. Results: For the Adult Body Phantom Console displayed dose was 16.03 mGy and estimated dose was found as16.40 mGy. For the Adult Head Phantom, console displayed dose was 32.40 mGy and estimated dose was found as 34.60 mGy. Between the estimated and console displayed doses for Adult Body Phantom and Adult Head Phantom a deviation was realized of 2.3% and 6.8% respectively. Conclusion: Hence CTDI of the above mentioned machine comply with reference value within a tolerance of ± 20 % according to Food and Drug Administration (FDA). Bangladesh J. Nuclear Med. 26(2): 172-176, 2023